Antimicrobial Activities of Five Strains Of Lactococcus Isolated from Beef Against Indicator Organisms of Public Health Significance - Olusegun Ayodele Olaoye (Turkish Journal of Agriculture: Food Science and Technology)
Five strains of Lactococcus, including L. garviae K2, L. piscium SU4, L. lactis subsp. cremoris E22, L. plantarum L7 and L. lactis subsp. hordinae E91 were screened for production of antimicrobial agents. The strains were also analysed for antimicrobial activities against spoilage and pathogenic organisms, including Staphylococcus aureus, Salmonella Typhimurium, Escherichia coli, Yersinia enterocolitica, Pseudomonas aeruginosa, Klebsiella pneumoniae, Listeria monocytogenes, Bacillus cereus and Pseudomonas fluorescens. Result revealed that L. piscium SU4, L. plantarum L7 and L. lactis subsp. cremoris E22 had lactic acid production (g/107 colony forming units, CFU) of 7.23, 7.20 and 7.19. The value of 6.83 recorded as lactic acid produced by L. garviae K2 was significantly different from those obtained for others. The highest acetic acid production (3.55 g/107 CFU) was recorded for L. garviae K2 while L. piscium SU4 had the lowest (2.99 g/107 CFU). L. lactis subsp. hordinae E91 had diacetyl production of 71.99 (µg/107 CFU), which was higher than those recorded for other Lactococcus strains. Test for antimicrobial activities showed that Escherichia coli NCTC 86, Yersinia enterocolitica NCTC 10460, Pseudomonas aeruginosa NCIMB 10848, Bacillus cereus NCTC 21113 and Pseudomonas flourescens recorded higher susceptibilities to the antimicrobial action of the Lactococcus strains than others; zones of inhibition of 5 mm and above were recorded for the indicator organisms compared to lower values (